The role and importance of large companies in the economy of the Republic of Serbia - Krstić, Saša; Fedajev, Aleksandra (Serbian Journal of Management, 2020)
In contemporary business conditions, advanced market economies are characterized by the increasing contribution of the SMEs sector to the economic development. Having that in mind, a large number of papers have been aimed at analyzing business doing in this sector in the last couple of years. In this way, the focus has been shifted from large business entities and their importance to the economic growth to the SMEs sector. In this regard, the aim of this paper is to examine the financial situation, the place and the role of large companies in the overall economy of the Republic of Serbia, where, having in mind the fact that it is a transition economy, large enterprises, both private and public, significantly contribute to the growth of the economic activity and employment. Before all, the degree of the liquidity, efficiency, indebtedness and profitability of these companies in the period 2014-2017 was determined by using the ratio analysis. After that, on the basis of the selected ratios, a comparative financial performance analysis of large business entities in relation to those small, medium-sized and micro- was carried out by applying the Entropy and the PROMETHEE II methods. The obtained results pointed out that large business entities had a favorable business economy in relation to the other groups of business entities by size, and their performances had improved to a certain extent in the observed period.